THE ROLE OF THE LINGUO-CULTURAL APPROACH IN TEACHING A FOREIGN LANGUAGE - Pirimbetov Abdulvakhaf Ikramovich, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article considers hypothetical underpinnings of the linguo-social methodology in showing a foreign language and useful execution of the linguo-social part in showing English in secondary school. Here is given the most consideration to phonetic and social elements in the growing experience and their job in the development of an open demonstration. As of late, a great deal of foreign language courses has shown up in our country, in the commercial of which you can frequently peruse: “You will know the language better than the English sovereign!” Yet a considerable lot of them underline just a mechanical comprehension of the language, without considering the real factors of the nation of the language or other significant elements. For a genuine capacity to peruse and comprehend the text, it is important to consider syntax and jargon, yet in addition a wide range of information on a phonetic and social nature, the real factors of the language, and so on. Different learning methodologies should arise. Keywords: Linguo-cultural approach in teaching, formation of language activity, development of speech, teaching perception, specific vocabulary, formation of language activity, national political culture